OSAS-Related Inflammatory Mechanisms of Liver Injury in Nonalcoholic Fatty Liver Disease - Elena Paschetta; Paola Belci; Anna Alisi; Daniela Liccardo; Renato Cutrera; Giovanni Musso; Valerio Nobili (Mediators of Inflammation)
Obstructive sleep apnoea syndrome (OSAS) is a common sleep disorder, affecting over 4% of the general population, and is associated with metabolic syndrome and cardiovascular disease, independent of obesity and traditional risk factors. OSAS has been recently connected to nonalcoholic fatty liver disease (NAFLD), the most common chronic liver disease in the world, which can be found in 30% of the general adult population. Several studies suggest that the chronic intermittent hypoxia (CIH) of OSAS patients may per se trigger liver injury, inflammation, and fibrogenesis, promoting NAFLD development and the progression from steatosis to steatohepatitis, cirrhosis, and hepatocellular carcinoma. In NAFLD patients, liver disease may be caused by hypoxia both indirectly by promoting inflammation and insulin resistance and directly by enhancing proinflammatory cytokine production and metabolic dysregulation in liver cells. In this review, we focus on molecular mechanisms linking OSAS to NAFLD, including hypoxia inducible factor (HIF), nuclear factor kappa B (NF-κB), YKL-40, unfolded protein response, and hypoxic adipose tissue inflammation, which all could provide novel potential therapeutic approaches for the management of NAFLD patients with OSAS.